Evaluation of the effects of chlorpyrifos combined with lipopolysaccharide stress on neuroinflammation and spatial memory in neonatal rats. (1st December 2018) - Wang, Peipei; Dai, Hongmei; Zhang, Chen; Tian, Jing; Deng, Yuanying; Zhao, Mengwen; Zhao, Mingyi; Bing, Guoying; Zhao, Lingling
Abstract: Chlorpyrifos (CPF) may weaken the immune defenses of children, making them vulnerable to opportunistic bacterial infection. CPF combined with bacterial infection is a potential problem for children during their childhood development. However, there is a lack of studies on the joint effects of these two factors on children. Here, we assessed the effects of CPF combined with lipopolysaccharide (LPS) on the inflammation and development of the nervous system. In this study, the cell toxicity of CPF plus LPS in cultured astrocytes, and the pathogenic effects of CPF plus LPS in neonatal rat models were observed. The hydrogen (H2 )-inhalation was used for treatment to explore its therapeutic potential. We found that CPF plus LPS activated the astrocyte, which increased the expressions of HMGB1, TLR4, and p-NF-κB p65, while H2 -inhalation reduced the expressions ( p  < 0.05). We also found that CPF plus LPS induced long-lasting spatial memory deficits throughout brain maturation. However, H2 -inhalation improved rat performance in these behavioral experiments ( p  < 0.05). In conclusion, the sub-toxic concentration of CPF did not cause a significant damage in short term, but induced a severe long-term damage to the brain when combined with LPS. H2 -inhalation reduced the neuronal damage and behavioral abnormalities caused by CPF and LPS exposure.